The Impact of a Loyalty Program on Credit Card Portfolio Performance: A Cluster-Based Analysis of Redeemers and Non-Redeemers in Q Rewards, Q-Bank Qatar - Davy Andriansyah H Sihotang; Atik Aprianingsih (Green Publisher Indonesia, 2026)
Qatar is one of the wealthiest nations globally, with a relatively small population of approximately 3 million. It has attracted nearly 20 active banks, resulting in a highly saturated and intensely competitive market. In Qatar’s market, Q-Bank positions the Q-Rewards loyalty program as a core strategic differentiator and has made significant investments to boost customer engagement and profitability. However, with rising reward liabilities, it is critical to assess whether the program contributes meaningfully to revenue generation. This research studies the effectiveness of Q-Bank (pseudonym), Qatar’s loyalty program, “Q-Rewards,” and its impact on credit card portfolio performance—based on the correlation between loyalty program engagement and profitability—through behavior-based customer segmentation. The research draws on credit card transaction data from Q-Bank customers between 2023 and 2024, using K-means clustering analysis in Tableau software. The research identifies five distinct behavioral and profitability clusters, each with unique characteristics in terms of loyalty engagement, spending categories, income, age, tenure, nationality, digital usage, and contribution to overall portfolio profitability. It reveals that redeemers—customers who utilize their loyalty points—tend to be significantly more engaged and profitable than non-redeemers, generating approximately 1.2 to 2.4 times higher profitability across all clusters. This finding demonstrates that redemption behavior correlates positively with profitability. This research also offers a practical framework for Q-Bank to optimize its loyalty program by implementing personalized engagement strategies, enabling the bank to better manage reward liabilities and strengthen its competitive positioning in Qatar’s dynamic banking environment.